THE EFFECTS OF E-COMMERCE BUSINESS IN TAX EXAMINATION, TAX SANCTIONS TOWARD TAX REVENUE - Shofia Kauni; Nadia Salsabillah (Journal Informatic, Education and Management (JIEM), 2026)
This research aims to find out about the The Effects Of E-Commerce Business In Tax Examination, Tax Sanctions Toward Tax Revenue “Empirical Study on Online Business in Aceh Tengah” that have been in Takengon City. This research used primary quantitative data, and the data was obtained from spared of questionnaires. The sample in this research was the owner and user of business on e-commerce in Takengon City. Respondents in this research are 101 people, 58.4% owner of business online on e-commerce and 41.6% user or buyer of business online on e-commerce. The sampling technique used in this research is simple random sampling technique. The data analysis technique used in this research is multiple linear regression using programs in IBM SPSS version 25.0. The result of this study that show, business on e-commerce have a positive and have significant effect on tax revenue, tax examination has positive effect but not have a significant effect and tax sanctions have positive effect and have significant effect on tax revenue in Takengon city.